Which recipient pretransplant factors, such as MELD, renal function, sarcopenia, and recent sepsis influence suitability for and outcome after living donor liver transplantation? A systematic review of the literature and expert panel recommendations. Issue 10 (9th December 2022) - Roll, Garrett R.; Spiro, Michael; Raptis, Dimitri Aristotle; Jalal, Arif; Yan, Cheung Tsz; Olthoff, Kim M.; Caicedo, Juan C.; Lee, Kwang‐Woong; Yagi, Shintaro; Cattral, Mark S.; Soin, Arvinder S.; ,
Abstract: Background: Varied access to deceased donors across the globe has resulted in differential living donor liver transplant (LDLT) practices and lack of consensus over the influence of models for end stage liver disease (MELD), renal function, sarcopenia, or recent infection on short‐term outcomes. Objectives: Consider these risk factors in relation to patient selection and provide recommendations. Data sources: Ovid MEDLINE, Embase, Scopus, Google Scholar, Cochrane Central. Methods: PRIMSA systematic review and GRADE. PROSPERO ID: RD42021260809 Results: MELD >25–30 alone is not a contraindication to LDLT, and multiple studies found no increase in short term mortality in high MELD patients. Contributing factors such as muscle mass, acute physiologic assessment and chronic health evaluation score, donor age, graft weight/recipient weight ratio, and inclusion of the middle hepatic vein in a right lobe graft influence morbidity and mortality in high MELD patients. Higher mortality is observed with pretransplant renal dysfunction, but short‐term mortality is rare. Sarcopenia and recent infection are not contraindications to LDLT. Morbidity and prolonged LOS are common, and more frequent in patients with renal dysfunction, nutritional deficiency or recent infection. Conclusions: When individual risk factors are studied mortality is low and graft loss is infrequent, but morbidity is common. MELD, especially with concomitant risk factors, had the greatest influence on short term outcome, and recent infection had the least. A multidisciplinary team of experts should carefully assess patients with multiple risk factors, and an optimal graft is recommended.